(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research examines how female intrasexual competition and internalized sexism are manifested in digital discourses surrounding birth and motherhood on TikTok (the Chinese version called Douyin) in China and Malaysia. Drawing on qualitative content analysis and in-depth interviews, the study reveals how platform algorithms, aesthetic norms, and social expectations shape women’s online self-presentation and peer judgment. The findings highlight the ideological tensions between traditional familism, neoliberal individualism, and feminist expression within digital motherhood culture. By comparing China and Malaysia, the paper underscores how cultural and policy environments influence women’s negotiation of reproductive identity and digital visibility. The study contributes to a deeper understanding of gendered digital governance and localized feminist dynamics in the Global South.